The importance of reputation for business firms from the perspective of their citizens - Bali, Asst.Prof. D. Ahmad Omar Bali; محمود, م.م. دیاری حامد محمود (Sulaimani Journal for Humanities, 2025)
The importance and value of corporate reputation has attracted researchers in the last two decades. This research attempts to identify the value of reputation to Kurdish business companies in the Kurdistan Region_ Iraq. In this study, data collected through survey and a questioner were sent out through social media groups. 560 participants randomly responded from (Erbil, Sulamimanyah, Duhok and Halabja) provinces. The most important findings of the study show that; first, quality is the most important component of decision making for buyers and customers when they first purchase a product. Second, participants strongly believe that companies only care about their profit and reputation does not matter to them.
Keywords: Importance; reputation; company reputation